2005
DOI: 10.1093/jaoac/88.3.935
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Determination of the Release Kinetics of Peptides and Free Amino Acids During the Digestion of Food Proteins

Abstract: The kinetics of peptide release during in vitro digestion of 4 protein sources (casein, cod protein, soy protein, and gluten) were investigated. Samples were sequentially hydrolyzed with pepsin (30 min) and pancreatin (2, 4, or 6 h) in a dialysis cell with continuous removal of digestion products. Nondialyzed digests were fractionated by ion-exchange chromatography and ultrafiltration. Animal proteins were digested at a greater rate than plant proteins. Target amino acids of specific enzymes appeared more rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…In this regard, we speculated that FM‐based diet can release more basic AA‐binding peptides than plant protein sources because of the high basic AAs content. Indeed, in vitro digestion by pepsin and pancreatin indicates that FM is tend to release more small molecular peptides than plant proteins (Savoie, Agudelo, Gauthier, Marin, & Pouliot, ). Therefore, compared with FM diet, the plant protein blend incorporation coupled with extra crystalline AAs in PP40 diet would release more free AAs after feeding which were absorbed by various AA transporters in the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we speculated that FM‐based diet can release more basic AA‐binding peptides than plant protein sources because of the high basic AAs content. Indeed, in vitro digestion by pepsin and pancreatin indicates that FM is tend to release more small molecular peptides than plant proteins (Savoie, Agudelo, Gauthier, Marin, & Pouliot, ). Therefore, compared with FM diet, the plant protein blend incorporation coupled with extra crystalline AAs in PP40 diet would release more free AAs after feeding which were absorbed by various AA transporters in the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…While animal nutritionists are more concerned with protein digestibility either true or apparent, digestive physiologists are more interested in the digestion process itself, as well as in the composition and amounts of products released to the intestinal lumen and potentially absorbed. (Savoie et al 2005). It seems that results obtained with in vitro assays that evaluate differences in the release rate of amino acids after hydrolysis (M arquez et al 2012) or their intestinal absorption (Mart ınez-Montaño et al 2010; Mart ınez-Montaño & Lazo 2012) avoiding the interference with intestinal microbiota can correlate better to the potential bioavailability of protein than to its in vivo digestibility measured under the conventional conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Picariello et al (2010) reported that peptides containing more neutral and basic AA underwent faster degradation compared with those with more acidic AA. Savoie et al (2005) observed that peptides rich in proline and glutamic acids are more resistant to pepsin and pancreatin activity. Burrell (1993) reported that peptides with the C-terminal end of lysine and arginine are preferentially cleaved by trypsin.…”
Section: Introductionmentioning
confidence: 99%